EVALUATION OF COREMAP PHASE 2 IN THE EASTERN INDONESIA BASED ON THE CHANGES IN CORAL COVERAGE - Giyanto, . (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2017)
COREMAP (Coral Reef Rehabilitation and Management Program) is a long-term program initiated by the Government of Indonesia to enhance the welfare of the coastal communities by protecting, rehabilitating, and achieving sustainable use of the Indonesian coral reefs and their associated ecosystems. COREMAP is three phases planned program. The first phase was launched in 1998 and finished in 2004. Phase 2 began in 2006 and ended in 2011. The last phase has started since the end of 2014 and will finish in 2019. One of the performance indicators of COREMAP phase 2 (COREMAP 2) was a significant improvement of live coral cover in 80% of all sampling sites. The aims of this study are to find out and evaluate the trend of live coral cover during COREMAP 2. Annual monitoring of coral reefs was conducted in all sites of COREMAP 2 in the eastern Indonesia. Those sites were: Pangkep, Selayar, Buton, Wakatobi, Sikka, Biak Numfor and Raja Ampat. Permanent transects were applied at each site. Life-form of benthic data including hard corals was collected using the Line Intercept Transect (LIT) method and surveyed using SCUBA diving equipment. The result indicates that all sites, except Biak Numfor, demonstrate improvement in live coral cover during COREMAP 2. In contrast, live coral cover in Biak Numfor shows a decline due primarily to storm damage, destruction by bombs, some bleaching, and predation by Acanthaster planci. An increase in live coral covers in six out of seven sites during COREMAP 2indicates that the activities of COREMAP 2 (e.g. public awareness, community-based MCS, alternative livelihood) has a positive impact on the management of coral reefs in the Eastern of Indonesia.